2017
DOI: 10.1186/s12936-017-2050-2
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in the production and use of DDT for control of malaria and other vector-borne diseases

Abstract: BackgroundDDT was among the initial persistent organic pollutants listed under the Stockholm Convention and continues to be used for control of malaria and other vector-borne diseases in accordance with its provisions on acceptable purposes. Trends in the production and use of DDT were evaluated over the period 2001–2014.ResultsAvailable data on global production of DDT showed a 32% decline over the reporting period, from 5144 to 3491 metric tons of active ingredient p.a. Similarly, global use of DDT, for cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(54 citation statements)
references
References 16 publications
1
51
2
Order By: Relevance
“…The second component, with a variance of 26.7%, showed loading scores of p,p′-DDT, and o,p′-DDT while the third component with a variation of 17.7% showed loading scores of δ-HCH, p,p′-DDE, and p,p′-DDD. In Africa, malaria remains an epidemic, and as a result, DDT, despite being discontinued for other uses, is still being used for the control of malaria [44]. The application of DDT pesticides in malaria control can, therefore, be ascertained to be a significant source of DDTs in this study [21].…”
Section: Resultsmentioning
confidence: 99%
“…The second component, with a variance of 26.7%, showed loading scores of p,p′-DDT, and o,p′-DDT while the third component with a variation of 17.7% showed loading scores of δ-HCH, p,p′-DDE, and p,p′-DDD. In Africa, malaria remains an epidemic, and as a result, DDT, despite being discontinued for other uses, is still being used for the control of malaria [44]. The application of DDT pesticides in malaria control can, therefore, be ascertained to be a significant source of DDTs in this study [21].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas use of DDT was officially banned in the U.S. and Norway in the early 1970s, its use for agricultural activities in China continued until the early 1980s and China continued to produce DDT for export through 2007. 34 In Singapore, general population exposure to DDT may have resulted from the importing of contaminated food, 35 including from Malaysia, which did not ban DDT until 1999. Risk of NHL in relation to total DDT or individual DDT metabolites has been evaluated in multiple prospective cohorts in Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that China was responsible for 20% of the total global production of DDT between 1950 and1983 [11,17,33]. DDT was banned in the United States in the early 1970s, and 10 years later DDT was also banned in Turkey,however, DDT has been used in sub-Saharan Africa until recently [22,27,29]. Further, a study showed that commercially available Dicofol, an acaricide, formulations could contain 14.3% of the total DDT and its degradation product, which could suggest that DDT contamination could also occur from Dicofol application [27].…”
Section: Introductionmentioning
confidence: 99%